2021
DOI: 10.1088/1755-1315/712/1/012038
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of brown macroalgae Sargassum ethanol extract from Lombok coast, Indonesia

Abstract: The coastal areas of Lombok has very high diversity of macroalgae which are largely unexplored. Among them are the brown macroalgae Sargassum species which are well known for their biological potentials. In this study, we aim to evaluate 4 Sargassum species, S.cristaefolium, S. crassifolium, S. polycystum, and S. aquifolium for their antioxidant potential of Sargassum species found the west coastal Aare of Lombok, Indonesia. To determine the antioxidant capacity of macroalgal extracts, 2,2-diphenyl-1-picrylhyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Brown macroalgae are well known to be rich in polyphenol compounds which potentially contribute to its antioxidant capacity 7 . The brown seaweed Sargassum species have shown strong antioxidant activity 8 . The brown macroalgae Sargassum cristaefolium is one of the most abundant Sargassum species in the coastal area of Lombok, Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…Brown macroalgae are well known to be rich in polyphenol compounds which potentially contribute to its antioxidant capacity 7 . The brown seaweed Sargassum species have shown strong antioxidant activity 8 . The brown macroalgae Sargassum cristaefolium is one of the most abundant Sargassum species in the coastal area of Lombok, Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…These inhibition concentrations are better than those obtained for D. dichotoma (IC 50 = 458.24 ± 2.98 µg·mL −1 ), found in the Gulf of Mannar, between southeast India and eastern Sri Lanka [ 74 ]. The highest effective concentration ever observed was even found in the study by Prasedya et al [ 75 ] for several species of Sargassum sp. (IC 50 = 737.30 ± 23.46 g·mL −1 ).…”
Section: Resultsmentioning
confidence: 85%
“…Clearly, phenolic compounds, in particular phlorotannins, appear as the major and most well studied group of compounds contributing to the antioxidant properties of Sargassum seaweeds. Indeed, positive correlations between phenolic content and antioxidant activity have been reported in many studies using whole algae, their parts, extracts, or fractions [ 74 , 75 , 76 , 77 ]. Notably, studies on phlorotannins isolated from Sargassum have shown that compounds, such as triphlorethol B, tetraphlorethol C, and pentaphlorethol A, can be more effective than certain antioxidant references such as ascorbic acid or resveratrol at preventing lipid peroxidation or scavenging of O 2 •− radicals [ 78 ].…”
Section: Bioactive Potential Of Sargassum Antioxidant Secondary Metab...mentioning
confidence: 99%